Penerapan Pemberian Asi Eksklusif dan MP-ASI Pada Pertumbuhan Balita di Desa Sidomulyo Kecamatan Biru-Biru Kabupaten Deli Serdang - manik, maria hermita; Samura, Maximilianus Dasril; Rosaulina, Meta; Hasian, Muhammad Tsawaby (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
The growth and development of babies is mainly influenced by the nutrients contained in breast milk, which include proteins, carbohydrates, minerals and vitamins which are important for health and growth. Entering the age of 6-24 months, toddlers' energy needs increase and require additional nutritional support through providing appropriate complementary foods (MP-ASI) to encourage optimal growth and development. The purpose of this public work is to secure exceptional breastfeeding and MP-ASI education in the growth of babies in the village of Sidomulyo and Deliserdang regency. This counseling is given to Mothers with children aged 0 to 5 years. Thirty-two mothers and toddlers participated in this outreach activity. It is hoped that this counseling can provide parents with an understanding of the importance of exclusive breastfeeding and how to provide MPASI appropriately to prevent the risk of malnutrition and stunting.